CircularWOOD – Towards Circularity in Timber Construction in the German Context. Issue 1 (1st September 2022) - Schuster, S; Geier, S
Abstract: The circular economy can pave the way to achieve ambitious sustainability goals. A major perpetrator of resource and material waste is the building sector. A lot of research results already provide innovative technologies and solutions for circular construction. However, what many of the circular economy initiatives in the construction sector have in common, is a certain malaise in moving from pilot projects with high individual engagement to actions on a larger scale. Prefabricated timber construction is one of the most promising key technologies towards a more resource efficient Europe. Despite this potential, downcycling or an early thermic utilization is common practice. Valuable resources are wasted and already captured CO2 is released. The research project circularWOOD aims to provide a better understanding for potentials and barriers in a first step. This paper outlines first findings. Prefabrication and element design facilitate circular construction approaches. The context in which stakeholder implement circular construction approaches is widened. A wide range of economic and ecological aspects is supplemented with cultural, political, and regulatory conditions. Under the premise of reuse with a minimum of necessary adaptation structural aspects are evaluated. The results show a current concentration on new construction with easy-to-implement design approaches. Further efforts towards strategies for the reuse of existing construction and experiences to facilitate the diffusion within the timber construction sector are required.